Peningkatan Kompetensi Siswa SMK melalui Pelatihan Dasar Programmable Logic Controller - Nabila Aulia Ramadhani; Gunawan, Arif; Syahrizal, Syahrizal; Syamsir, Hendri Novia; Sahar, Muzni (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2025)
This community service program was carried out at SMK Negeri 1 Minas to improve students’ competence in understanding and operating control systems based on Programmable Logic Controllers. The target participants were 20 students from the Electrical Power Installation and Air Conditioning and Refrigeration Engineering Departments who had limited skills in basic programming and industrial automation applications. The program adopted an educational and training approach through a structured workshop covering sequential logic, basic programming instructions such as timer, counter, comparison, arithmetic, and the introduction of human-machine interface systems. Evaluation was conducted through pretest and posttest, as well as a Likert-scale feedback questionnaire. The results indicated a significant improvement in student performance, with the average score increasing from 43.46 to 79.49, representing an 82.87% improvement. Participants also expressed a very high level of satisfaction with the materials, instructors, and hands-on sessions. Overall, this training program effectively enhanced students’ fundamental understanding and practical skills in automation control, thereby strengthening their readiness to enter the technology-driven industrial workforce.